The Role Of Financial Management Knowledge In Mediating Financial Technology, Financial Literacy And Self-Efficacy On The Performance Of Culinary UMKM In Kediri City - Umi Nadhiroh; Agus Hermawan (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to find out that financial technology, self-efficacy, and financial literacy can influence the performance of culinary micro, small, and medium units (MSMEs) and to find out the role of financial management knowledge in mediating this. The research design used quantitative methods. The subjects of this research are culinary MSME entrepreneurs who have used financial technology in their business transactions. This research used questionnaires that were distributed directly as data collection material. The sample in this study was 90 respondents, who were analyzed using SmartPLS. The results of this study show that financial technology, financial literacy and self-efficacy do not have a direct positive effect on the performance of culinary MSMEs. The results of this research also show that financial technology and financial literacy do not have a direct positive effect on financial management knowledge. But efficacy can have a direct positive effect on financial management knowledge. The results of this research also illustrate that Financial Management Knowledge is unable to mediate Financial Technology, Financial Literacy, and Self-Efficacy on MSME Performance.